2018
DOI: 10.18311/jbc/2018/21359
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nematicidal properties of fluorescent pseudomonads using peanut root-knot nematode, Meloidogyne arenaria

Abstract: The primary objective of this study was to identify natural isolates of fluorescent pseudomonads with superior antagonistic activity towards plant parasitic nematodes. Nematicidal potential of eighteen isolates of fluorescent pseudomonads were compared against peanut root-knot nematode, Meloidogyne arenaria. Cell-free culture filtrate of DAPG-producing isolates of Pseudomonas putida caused significantly higher mortality of M. arenaria (J2) with highest in isolate DAPG3 (87.36%), followed by DAPG1 (84.16%) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Our study results indicated that liquid formulation of P. putida have a greater nematicidal potential against M. incognita infecting okra under field conditions. Earlier study also demonstrated that, DAPG producing P. putida shown strong nematicidal activity against Meloidogyne arenaria by causing highest juvenile mortality under in-vitro and reducing 51% of root galls when applied in combination of seed treatment and soil application under in-vivo conditions (Holajjer et al 2018). Similarly, Pseudomonas spp., such as P. fluorescens and P. putida applied in combination of seed treatment 10 g/ kg seed and neem cake @1 t/ha significantly reduced the number Treatment details: T1: Seed treatment with Bacillus pumilus 1% A.S. @ 10 mL/ kg seed, T2: Seed treatment with Pseudomonas putida 1% A.S. @ 10 mL/ kg seed, T3: T1+ application of 20 tonnes of FYM enriched with 5 L of B. pumilus/ ha, T4: T2+ application of 20 tonnes of FYM enriched with 5 L of P. putida/ ha, T5: Application of FYM20 t/ha, T6: Chemical treatment (Carbofuran 3G at 1 kg a.i./ha), T7: Chemical treatment (Carbofuran 3G at 1 kg a.i./ha) +FYM 20 t/ha, T8: Control.…”
Section: Resultsmentioning
confidence: 86%
“…Our study results indicated that liquid formulation of P. putida have a greater nematicidal potential against M. incognita infecting okra under field conditions. Earlier study also demonstrated that, DAPG producing P. putida shown strong nematicidal activity against Meloidogyne arenaria by causing highest juvenile mortality under in-vitro and reducing 51% of root galls when applied in combination of seed treatment and soil application under in-vivo conditions (Holajjer et al 2018). Similarly, Pseudomonas spp., such as P. fluorescens and P. putida applied in combination of seed treatment 10 g/ kg seed and neem cake @1 t/ha significantly reduced the number Treatment details: T1: Seed treatment with Bacillus pumilus 1% A.S. @ 10 mL/ kg seed, T2: Seed treatment with Pseudomonas putida 1% A.S. @ 10 mL/ kg seed, T3: T1+ application of 20 tonnes of FYM enriched with 5 L of B. pumilus/ ha, T4: T2+ application of 20 tonnes of FYM enriched with 5 L of P. putida/ ha, T5: Application of FYM20 t/ha, T6: Chemical treatment (Carbofuran 3G at 1 kg a.i./ha), T7: Chemical treatment (Carbofuran 3G at 1 kg a.i./ha) +FYM 20 t/ha, T8: Control.…”
Section: Resultsmentioning
confidence: 86%